Between Words and Wisdom: Exploring Explicit and Implicit Meanings in the Ulumul Qur'an - Elisa Rahmah; Muhammad Shohib (Islamic Journal of Communication and Public Discourse, 2026)
Background: The Qur’an, as the primary source of Islamic teachings, contains both explicit (manṭūq) and implicit (mafhūm) meanings. An imbalance in understanding these two dimensions often leads to rigid textualism or speculative interpretation, posing significant challenges in contemporary Qur’anic hermeneutics. Objective: This article aims to analyze the typological structures of manṭūq and mafhūm within the Ulumul Qur’an tradition, explain the relationship between lafaz (wording) and hikmah (wisdom) from the perspective of explicit and implicit meaning and examine the implications of this integrative understanding for Islamic education, character formation, social life, and spiritual development. Method: This study employs a qualitative library research design with a descriptive-analytical approach, utilizing thematic-conceptual analysis of classical and contemporary Ulumul Qur’an literature and tafsir works. Results: Explicit meaning (manṭūq) functions as a normative basis and methodological boundary for interpretation, while implicit meaning (mafhūm) represents the wisdom and substantive purpose of the Qur’an. Their integration yields an authentic and contextual understanding. Findings and Implications: This integrative hermeneutical framework supports holistic Islamic education, value-based character formation, socially just communities, and deeper spiritual life. The novelty of this study lies in its systematic linkage of the manṭūq-mafhūm dichotomy with the lafaz-hikmah relationship as a unified methodological principle for authentic and contextual Qur’anic interpretation. Conclusion: The study concludes that integrating the manṭūq–mafhūm framework with the relationship between lafaz and hikmah provides a comprehensive hermeneutical principle that bridges textual authenticity and contextual relevance.